Amniotic diversity of Taranga Hill-forest, Gujarat, India - Patel, C.D.; Patel, M.I. (Our Nature, 2011)
Amniotes is the group of the animals’ viz., reptiles, birds and mammals, in which extra-embryonic membranes are developed around the embryo for different functions. Amniotic diversity of Taranga Hill-forest (THf) has been studied. THf was represented by 147 species belonging to 116 genera and 62 families. Of these, 24 species were reptiles (belonging 21 genus and 11 families), 98 species were birds (belonging 73 genus and 35 families) and 25 species were mammals (belonging 22 genus and 16 families). It shows that THf has good amniotic diversity. The THf covers 21.21% amniotic diversity of Gujarat and 7.07% of India. The total amniotic diversity of THf was covered by 66.67% species of birds, 17.01% species of mammals and 16.33% species of reptiles. Of the total 62 families, 6 families have high diversity, 18 families have moderate diversity, 10 families have low diversity and 28 families have very low diversity. The high-diversified six families were Colubridae, Accipitridae, Corvidae, Muscicapidae, Sylviidae and Passeridae. Diversity in an area is dependent upon the availability of variable food sources, habitats for roosting, resting, breeding and sheltering; semi-arid climate and evolutionary history of the Aravalli ranges. DOI: 10.3126/on.v8i1.4322